The Effect of Trust and Product Quality on Repurchase Intention for Yamalube Oil Products in Gresik Regency - Muhammad Harun Alrasyid; Sugeng Purwanto; Wilma Cordelia Izaak (PT Inovasi Pratama Internasional, 2023)
In line with the automotive industry's unstoppable growth, a pervasive phenomenon of counterfeit lubricants and motorcycle oils circulating in the market has emerged, with some of them increasingly mimicking the appearance of genuine oil products. Counterfeit oil manufacturers not only imitate various characteristics of the packaging but also innovate by replicating the label technology developed by reputable oil brands. This has caused consumers to worry about the quality of the products and lose trust in several well-known oil brands. Therefore, researchers became interested in conducting a study on the variables of Trust and Product Quality influencing repurchase intention. This study utilized a quantitative descriptive research approach and non-probability sampling with a purposive sample strategy among 105 users of Yamalube Oil products in Gresik Regency. All hypotheses in this study were investigated using component-based SEM analysis with PLS. The research instrument in this study was an online questionnaire created using Google Forms. Based on statistical calculations, the researchers found that Trust and product quality significantly effect repurchase intention for Yamalube oil products in Gresik Regency. The results of this study explain that the repurchase intention variable, effected by the independent variables of Trust and Product Quality, accounts for 88,9% of the variance, while the remaining 11,1% is explained by other variables outside the scope of this study.